Variational multirate integration in discrete mechanics and optimal control - Gail, T; Ober-Blobaum, S; Leyendecker, S (ECCOMAS, 2017)
Systems with dynamics on different time scales have contradicting requirements on the integrator. These can be resolved with a multirate integration approach, where the system is split in parts which are integrated with different methods and time steps. This leads to computing time savings compared to a highly accurate simulation of the complete system. In this work, we benefit from these savings for optimal control problem simulations. Based on DMOC, which is a structure preserving simulation method for optimal control problems in mechanics, we develop an optimal control simulation method with a variational multirate integration scheme. Via an example system, we show convergence and the computing time behaviour of the multirate optimal control simulation method.